Increasing access to renal transplantation in India through our single‐center kidney paired donation program: a model for the developing world to prevent commercial transplantation. (22nd August 2014) - Kute, Vivek B.; Shah, Priyadarshini S.; Vanikar, Aruna V.; Gumber, Manoj R.; Patel, Himanshu V.; Engineer, Divyesh P.; Shah, Pankaj R.; Modi, Pranjal R.; Shah, Veena R; Rizvi, Syed Jamal; Trivedi, Hargovind L.
Summary Because access to transplantation with HLA‐desensitization protocols and ABO incompatible transplantation is very limited due to high costs and increased risk of infections from more intense immunosuppression, kidney paired donation (KPD) promises hope to a growing number of end‐stage renal disease (ESRD) patient in India. We present a government and institutional ethical review board approved study of 56 ESRD patients [25 two‐way and 2 three‐way pairs] who consented to participate in KPD transplantation at our center in 2013, performed to avoid blood group incompatibility (n = 52) or positive cross‐match (n = 4). All patients had anatomic, functional, and immunologically comparable donors. The waiting time in KPD was short as compared to deceased donor transplantation. Laparoscopic donor nephrectomy was performed in 54 donors. Donor relationships were spousal (n = 40), parental (n = 13), others (n = 3), with median HLA match of 1. Graft survival was 97.5%. Three patients died with functioning graft. 16% had biopsy‐proven acute rejection. Mean serum creatinine was 1.2 mg/dl at 0.73 ± 0.32 months follow‐up. KPD is a viable, legal, and rapidly growing modality for facilitating LDRT for patients who are incompatible with their healthy, willing living donor. To our knowledge, this is the largest single‐center report from India.